Pokdarwis Organization Communication Training In Cireundeu Traditional Village Management - Sunarja, Darmawan; Simanjuntak, Diana (Universitas Muhammadiyah Jember, 2024)
Organizational communication in Kampung Adat Cireundeu is one of the important things for disseminating information effectively through Pokdarwis. Pokdarwis does not have knowledge and experience regarding Organizational Communication skills, so they do not understand how to communicate based on the organizational hierarchy, for example to superiors, to subordinates, internally and externally. This research aims to strengthen, deepen and effectiveness the Pokdarwis communication function. The method used is a case study through community service activities. Based on the research results, the Pokdarwis Organizational Communication capability has characteristics and uniqueness compared to formal Organizational Communication in companies, government, business and so on. They have conceptual/theoretical Organizational Communication Capabilities but technically operationally they have two philosophies of local wisdom that differentiate them from other organizations.